2017
DOI: 10.1016/j.yhbeh.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence that acute stress moderates basal testosterone's association with retaliatory behavior

Abstract: A contribution to a special issue on Hormones and Human Competition. Testosterone is theorized to increase retaliation after social provocation. However, empirical evidence in support of these theories is mixed. The present research investigated whether acute stress causally suppresses testosterone's association with retaliation. We also explored sex differences in behavioral responses to acute stress. Thirty-nine participants (51.28% male) were randomly assigned to a high- or low-stress condition. Then partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 106 publications
3
37
1
Order By: Relevance
“…Despite these mean differences, the authors found positive correlations between testosterone and self-reported aggression in both women and men. Thus, although aggression and testosterone may be lower in women than men, many studies observed the same positive relationships between testosterone and aggression in women as they do in men (e.g., Prasad et al, 2017 ; Probst et al, 2018 ). A study of 12 women in a double-blind placebo-controlled testosterone administration study suggests that testosterone may increase aggression because it reduces sensitivity to punishment and increases reward sensitivity (van Honk et al, 2004 ).…”
Section: Part 2: Neurobiological Pathways To Women’s Aggressionmentioning
confidence: 94%
“…Despite these mean differences, the authors found positive correlations between testosterone and self-reported aggression in both women and men. Thus, although aggression and testosterone may be lower in women than men, many studies observed the same positive relationships between testosterone and aggression in women as they do in men (e.g., Prasad et al, 2017 ; Probst et al, 2018 ). A study of 12 women in a double-blind placebo-controlled testosterone administration study suggests that testosterone may increase aggression because it reduces sensitivity to punishment and increases reward sensitivity (van Honk et al, 2004 ).…”
Section: Part 2: Neurobiological Pathways To Women’s Aggressionmentioning
confidence: 94%
“…Future work interested in examining testosterone treatment's interaction with cortisol change dynamics as predictors of competitive decision-making will require study designs that measure or manipulate acute cortisol change prior to a competitive decision-making task (e.g. Prasad et al, 2017).…”
Section: Dual-hormone Effects With Other Cortisol Measuresmentioning
confidence: 99%
“…However, if the prosocial behavior is directed at someone belonging to the participant’s in-group (e.g., a friend), higher testosterone is associated with more cooperative behavior in males [84, 91, 92]. In women, the link between testosterone and prosocial behavior is mixed, with studies reporting a negative association [93], in one case following mild stress [87] and a positive association [93, 94], in one case only when reciprocating generosity [93]. Although the association between testosterone in prosocial behavior per se has not been studied across adolescence, there is a positive relationship between testosterone and antisocial behavior that intensifies across adolescence in males, but not females, which may be informed by social experiences and higher fetal exposure to testosterone [95].…”
Section: Oxytocin and Testosteronementioning
confidence: 99%